2008
DOI: 10.4103/1319-3767.43275
|View full text |Cite
|
Sign up to set email alerts
|

Past, present and future of colorectal cancer in the Kingdom of Saudi Arabia

Abstract: Background/Aims:The crude frequency of colorectal cancer (CRC) is second to breast cancer in the Kingdom of Saudi Arabia (KSA). To assess the future burden of CRC in the country, we designed a model that takes into consideration the recent lifestyle pattern and the growth and aging of the population.Methods:We compared CRC statistics for KSA (using data from the National Cancer Registry) with that from the Surveillance, Epidemiology and End Results (SEER) databases of the United States of America (USA). We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 29 publications
3
82
0
Order By: Relevance
“…Nevertheless, this finding is comparable to other studies carried out in Saudi Arabia, suggested the possibility for the presence of a familial risk factors for the development of CRC among Saudis for which more controlled and validated studies are warranted (Mansoor et al, 2002;Al Jabreen, 2007). The current recommendation for CRC screening at the age of 50 would be of very questionable reliability as a high proportion of those patients will not be diagnosed by the time of the proposed screening (Mansoor et al, 2002;Ibrahim et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Nevertheless, this finding is comparable to other studies carried out in Saudi Arabia, suggested the possibility for the presence of a familial risk factors for the development of CRC among Saudis for which more controlled and validated studies are warranted (Mansoor et al, 2002;Al Jabreen, 2007). The current recommendation for CRC screening at the age of 50 would be of very questionable reliability as a high proportion of those patients will not be diagnosed by the time of the proposed screening (Mansoor et al, 2002;Ibrahim et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
“…Ibrahim et al (2008) postulated correlation of changing trends in incidence and mortality of CRC with high and low rates areas, globally. The incidence is increasing much faster in areas where rate was formerly low, as in case of KSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saudi Arabia, CRC incidence, morbidity and related mortality have been steadily increasing over the past twenty years (Ibrahim et al, 2008). There were 904 new cases of CRC accounting for 10.2 % of all newly diagnosed cancer patients in 2008 (Bazarbashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%